question 4
give right answer
Attachments:
![](https://hi-static.z-dn.net/files/da6/07aad424d37b6613205ed1c580dc43d3.jpg)
amanchakrawarty:
question 5 also
Answers
Answered by
1
P(x) = x^2 - 4x
substitute x = 0
P(0) = 0 - 4*0 = 0
substitute x = 4
P(4) = 4^2 - 4*4
P(4) = 16 - 16 = 0
Hope it helped you
Ans 5:
P(x) = x^2 - 2x
= x(x-2) = 0
= x = 0 , 2
substitute x = 0
P(0) = 0 - 4*0 = 0
substitute x = 4
P(4) = 4^2 - 4*4
P(4) = 16 - 16 = 0
Hope it helped you
Ans 5:
P(x) = x^2 - 2x
= x(x-2) = 0
= x = 0 , 2
Similar questions